Analise de tráfego de duas interseções da cidade de Belém usando simulação - DIAS, Ranieri Araújo Farias (2024)
The present work carried out the study of the intersections of Avenidas Tavares Bastos, and Rodolfo Chermont, and Rodolfo Chermont and Rua da Mata in the city of Belém-PA and aims to propose improvements through the use of micro traffic simulation. The work presents data collection through volumetric counting via videotape and data processing with Excel and the Simulation of Urban Mobility (SUMO) software, where traffic engineering tools were applied to provide solutions at the study intersections. The results were satisfactory, as they helped in decision-making regarding which sections of the roads require greater road capacity, as through the analysis of the road's traffic capacity it was possible to observe that in the scenario where the addition of new lanes was suggested, the road capacity became greater than the current flow at the intersection's main peak hours. In addition to being a free tool, SUMO can enable low-cost interventions, as it is possible to create simulations where the geometry of the road is not changed, or even changes in the traffic light cycle, where the size of vehicle queues can be analyzed when the stage of the traffic light cycle does not allow movement.